Réponses

2014-09-29T12:26:32+02:00
1) 3 solutions => x-1 = 0 ; soit x = 1
x - 2 = 0 soit x = 2
X - 3 = 0, soit x = 3
2) 2x+1 = -3 + 21 donc 2x = -3 + 21 -1 ; 2x = 17 ; x = 17/2 = 8,5
3) (x+1)² = x² + 18 => x²+2x+1 = x² +18 => x² -x² +2x = 18-1 => 2x = 17 => x = 17/2 = 8,5
(X+1)^2=x^2+18 x^2+2x+1=x2+18
erreur de frappe, j'efface tout (x+1)^2=x^2+18 d'ou x^2+2x+1=x^2+18 soit 2x=17 et x=17/2
Meilleure réponse !
2014-09-29T13:26:32+02:00
Bonjour
1)
(x-1)(x-2)(x-3) = 0    produit de facteurs est nul si un facteur est nul 
soit     x-1 = 0    pour x = 1
soit     x-2 = 0    pour x = 2 
soit     x-3 = 0     pour x = 3 
l'ensemble S : { 1 ; 2 ; 3 } 
2)
2x+1 = -3x+21 
5x = 20 
x = 20/5 = 4      
l'ensemble S : { 4 } 
3)
(x+1)² = x² + 18 
(x²+2x+1)-x²-18 = 0 
2x - 17 = 0 
x = 17/2
l'ensemble S : { 17/2 } 
Bonne journée